2011
DOI: 10.1007/s11240-011-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

Genotype- and age-dependent patterns of lignin and cellulose in regenerants derived from 80-year-old trees of black mulberry (Morus nigra L.)

Abstract: Proliferating shoot cultures of black mulberry (Morus nigra), derived from axillary buds of two donor trees designated as Mn1 and Mn2, more than 80 years of age, were established in vitro. Subsequently, shoot-tips were used to induce both axillary and adventitious shoot regeneration following incubation on Murashige and Skoog medium containing 14 different treatments of various concentrations of plant growth regulators, including 6-benzyladenine (BA), thidiazuron (TDZ), and combinations of BA with indole-3-but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
4
8
0
Order By: Relevance
“…Lignin deposition is related to the age of the plant. Durkovic et al (2011) reports that 3-year-old plants have higher concentrations of lignin than 1-year-old plants [43]. Further, callus cells in roots have a higher lignin content than meristem [44].…”
Section: Discussionmentioning
confidence: 99%
“…Lignin deposition is related to the age of the plant. Durkovic et al (2011) reports that 3-year-old plants have higher concentrations of lignin than 1-year-old plants [43]. Further, callus cells in roots have a higher lignin content than meristem [44].…”
Section: Discussionmentioning
confidence: 99%
“…Lignin deposition is related to the age of the plant. Durkovic et al [47] reported that 3-year-old plants have higher concentrations of lignin than 1-year-old plants. Further, callus cells in roots have higher lignin content than meristem [48].…”
Section: Discussionmentioning
confidence: 99%
“…Wood has special mechanical and acoustical properties, and this had been traditionally used in the field of musical instruments making (Endo et al 2016). As it has generally been considered in scientific studies, mainly based on Western/globalised cultures, suitable wood for making stringed musical instruments would often be defined by higher modulus of elasticity (E) per specific gravity (γ), and by lower damping by internal friction (tanδ) than other woods (Ono & Norimoto 1983).…”
Section: Introductionmentioning
confidence: 99%
“…It is often argued that musical instrument makers and artisans would consider aged wood as a material with improved physical and acoustical properties such as reduced moisture expansion and damping (Endo et al 2016, Obataya 2017. Two interesting studies show some "improvement" in the acoustical properties of long-term aged pine wood (Noguchi et al 2012) or spruce wood (Obataya et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation